Inhibition of USP22 by miR-200b-5p represses gastric cancer cell proliferation and migration by targeting the NF-κB signaling pathway - Guo Yingying; Zhang Panpan; Gao Zhixing; Liu Xiaotian; Su Chen; Chen Su; An Tao; Hou Jingjing (Acta Biochimica et Biophysica Sinica, 2024)
Gastric cancer (GC) is an aggressive tumor type with an intricate pathogenesis and limited therapeutic options. Ubiquitin-specific protease 22 (USP22) is a protein implicated in cell proliferation, metastasis, and tumorigenesis. However, the regulatory mechanisms governing USP22 in GC are still not fully understood. In this study, we perform bioinformatics analysis to identify conserved miRNA recognition sites for miR-200b-5p within the 3′UTR of USP22. Validation via luciferase reporter assay confirms the transcriptional regulation of USP22 by miR-200b-5p. Overexpression of miR-200b-5p markedly inhibits the proliferation and migration of GC cells in vitro and suppresses tumor growth in vivo. Conversely, ectopic expression of USP22 reversed this effect by modulating the NF-κB signaling pathway. Additionally, qPCR analysis reveals an inverse correlation between the miR-200b-5p level and USP22 expression in GC. Collectively, our findings indicate that miR-200b-5p-mediated inhibition of USP22 attenuates cell proliferation by targeting the NF-κB signaling pathway in GC, suggesting that miR-200b-5p and USP22 could serve as potential diagnostic or therapeutic targets for gastric cancer and other related human diseases.